2000
DOI: 10.1677/jme.0.0250129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketoacidosis on rat apolipoprotein A1 gene expression: a link with acidosis but not with ketones

Abstract: To determine if ketoacidosis contributes to reduced apolipoprotein A1 (apoA1) expression in insulindeficient diabetic rats, we examined the regulation of apoA1 gene expression in response to changes in ambient pH or ketone body concentrations. Hepatic apoAI mRNA levels were reduced 42% in diabetic rats relative to nondiabetic controls (means ..; 321·8 43·7 vs 438·7 58·8 arbitrary units; P<0·03). Neither endogenous apoA1 mRNA nor transcriptional activity of the rat apoA1 gene promoter (from 474 to 7) were alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
(25 reference statements)
4
15
0
Order By: Relevance
“…We have recently shown that apoA 1 mRNA content and apoA 1 promoter activity are suppressed by acidosis in both Caco-2 intestinal cells and HepG2 hepatocytes (Haas et al 2000). To confirm and extend our previous findings, apoA 1 protein content in HepG2 cells was measured by western blotting.…”
Section: Effect Of Acidosis On Apoa 1 Protein Contentsupporting
confidence: 54%
See 4 more Smart Citations
“…We have recently shown that apoA 1 mRNA content and apoA 1 promoter activity are suppressed by acidosis in both Caco-2 intestinal cells and HepG2 hepatocytes (Haas et al 2000). To confirm and extend our previous findings, apoA 1 protein content in HepG2 cells was measured by western blotting.…”
Section: Effect Of Acidosis On Apoa 1 Protein Contentsupporting
confidence: 54%
“…Quantitation of the results with a densitometer showed that acidosis reduced apoA 1 protein concentrations in HepG2 cells nearly 20%, from 100 2·3% to 80·3 5·4% (P<0·01). In this cell line, apoA 1 mRNA levels are also reduced by acidosis, by 20% (Haas et al 2000). This suggests that the steady-state apoA 1 protein concentration is likely to be directly related to the decrease in apoA 1 mRNA levels.…”
Section: Effect Of Acidosis On Apoa 1 Protein Contentmentioning
confidence: 58%
See 3 more Smart Citations